Experimental study of rectangular floating breakwater - Ariati Satriani (2013)
In order to reduce the reliance on oil and natural gas which are getting scarce as a source of energy many has research on an alternative so as to ensure these natural resources will not be used out. Among many alternative sources of energy, this report will focus on the wave energy. Building the equipment to harvest wave energy is expensive hence in order to make the system financially feasible, the equipment can be built together with other coastal structure such as breakwater. In Singapore context many of this breakwater structures are built to protect the harbour. The objectives of this research is to find out the effect of the distance between the harbour wall and the breakwater structure to the wave energy converter equipment which is placed together with the breakwater structure. Hence finding out the effective distance between the harbour wall and the breakwater structure so as to ensure minimal interference to the wave energy harvesting equipment without compromising the function of the breakwater. The experiment will be done in a controlled environment using a wave generator. Other factors that might interfere with the results were minimised as much as possible. The results are recorded using labview and dewesoft and analysed using MatLab. Using the software, the pressure and power output per unit width are obtained. The distance that yield the most power output without compromising the function of the breakwater is the most efficient distance. The results of the experiment would help the construction of the wave energy harvesting equipment and breakwater structure in terms of choosing the most efficient distance between the harbour wall and the breakwater structure so as to maximise the wave energy harvested.